Focus Group Discussion: how many Participants in a Group? - Michela Cortini; Teresa Galanti; Stefania Fantinelli (University of Bologna, 2019)
Focus group technique is often described as a subaltern procedure for collecting and analysing data, underestimating the FG great value; today this method has such a big scientific reputation that it is widely applied in different social research areas such as marketing, education, communication. This theoretical study aims at deeply analyze the matter about the right number of participants for a focus group; this methodological consideration can provide useful elements in order to balance risks and benefits when planning qualitative research in social context. In addition to the numerosity matter there are some elements to carefully consider for an effective focus group research: the sensitivity of themes, the scope of the research, the recording setting, the social category of both participants and researcher, the client.